Pengabdian Masyarakat Penguatan Local-Based Branding UMKM di Rempang Eco City - Jumsurizal Jumsurizal; Siti Rahmawati; Surya Laia; Deva Tanti Harahap; Mega Ananda Putri; Mohd Dainel Hizad; Sri Supri Hartini; Sudaberi Sudaberi; Ketrine Audre Sinaga; Sinta Safira Munahar; Sudirmawati Laia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The Rempang Eco City area in Batam City has great potential for SMEs, especially in the culinary and local product sectors. However, the development of SMEs in this area is still limited due to a lack of knowledge about product packaging and minimal use of digital technology for marketing. The mentoring program conducted by KKN student group 62 aims to improve the competitiveness of SMEs through strengthening more modern packaging and digital marketing strategies using social media, especially Instagram. The method used is a qualitative approach with participatory observation, in-depth interviews, and group discussions. The stages of activities include an initial survey to map the potential and conditions of MSMEs, conducting workshops and training on product design, packaging, and digital marketing, as well as direct assistance in creating and managing social media accounts. The results of the activities show an improvement in the ability of MSME actors to create attractive packaging designs, manage social media as a product showcase, as well as increased digital interaction with consumers. This program successfully increased the selling value of products, expanded market reach, and built the confidence of MSME actors. Although there are challenges related to digital literacy and creativity, this program has a positive long-term impact in promoting economic independence in the community and strengthening local cultural identity in Rempang Eco City.